Implementation of the Indonesian Minister of Education and Culture Regulation Number 1 of 2021 Regarding the Admission of New Students - Reviandi, Reviandi; Hariadi, Berian; Mulia, Rizki Afri; Meilina, Susiyanti; Putri, Rianda Prima (Adabi : Journal of Public Administration and Business, 2024)
This research examines the execution of the zoning-based New Student Admissions (PPDB) policy at SMA Negeri 2 Padang, in alignment with the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 1 of 2021. This policy aims to enhance equitable access to and the quality of education across Indonesia, stipulating that schools must admit a minimum of 50% of new students through the zoning pathway, which is determined by residential proximity. Nonetheless, enacting this policy encounters many challenges affecting educational institutions, local government bodies, and the broader community. This study employs a qualitative descriptive methodology, utilizing comprehensive interviews with school principals, educators, PPDB committee members, parents of students, and representatives from the Education Office. Additionally, data collection methods encompass the analysis of relevant policy documents and direct observational research. The findings indicate significant impediments to policy dissemination and the technical dimensions related to zoning. Numerous parents express confusion regarding the metrics for distance measurement and the allocation of quotas for academic achievement, affirmative action, and transfer pathways. The inadequacy of school infrastructure further contributes to public discontent. Despite the policy’s intent to foster equity, the perception of preferred schools persists. Enhanced dissemination of information, rigorous policy oversight, and infrastructural enhancements are imperative in educational institutions in less developed areas to effectively realize the objective of educational equity.